Human capital in Spain and its distribution by provinces (1964-2013) - Serrano, Lorenzo; Soler, Ángel (REGION, 2015)
The regularly-updated database "Human capital in Spain and its distribution by provinces" provides information about the accumulation of human capital in Spain over the last five decades. The human capital estimates included in this database contain a wide range of information on how education levels in Spain have evolved, classified according to the level of studies completed and other human capital indicators. The database includes information that has been updated until the second trimester of 2013. It can be accessed at http://www.ivie.es/en/banco/caphum/series.php.